Effect of natural rainfall on the migration characteristics of runoff and sediment on purple soil sloping cropland during different planting stages - Yi Wang (IWA Publishing, 2021)
Due to the difficulty in monitoring subsurface runoff and sediment migration, their loss loads are still not clear and need further study. This study monitored water and soil loss occurring within experimental field plots for two calendar years under natural rainfall events. The sediment loss load was quantified by considering the corresponding water flow flux and its sediment concentration. The results showed that 60.04% of the runoff and 2.83% of the sediment were lost underground. The annual underground sediment loss reached up to 54.6 kg*ha−1*yr−1. A total of 69.68% of the runoff yield and 67.25% of the sediment yield were produced during the corn planting stage (CPS: March–July). Heavy rain and torrential rain events produced 94.45%, 65.46% of the annual runoff and 94.45%, 76.21% of the sediment yields during the corn-planting stage and summer fallow period (SFP: August–September). The rain frequency, rainfall, and rainfall duration of each planting stage significantly affected the resulting runoff and sediment yield. Measures aimed at the prevention and control of water-soil loss from purple soil sloping land should focus heavily on torrential rain and heavy rain events during the CPS and SFP. This paper aims to provide a practical reference for quantifying the water and soil loss from purple soil sloping cropland. HIGHLIGHTS Subsurface loss was more than 60% of total water loss of purple soil sloping cropland.; Annual accumulated underground sediment loss was considerable and noteworthy.; Surface and subsurface water and soil loss mainly happened in the corn planting stage.; Rainfall pattern controls the surface and subsurface loss of water and soil.;